Human Resource Competency Tourism Bali together with ASEAN Economic Community - Brata, Ida Bagus; Pemayun, A.A. Gde Putra (International Research Journal of Management, IT & Social Sciences, 2018)
The human resources capacity of Bali tourism is abundant, but in its management is still very far behind with neighboring countries such as Singapore, Malaysia, Thailand, Philippines, and other countries. This is due to the level of education that is still at the level of standards and facilities that are inadequate, resulting in a standard quality of tourism workforce, increased unemployment, decreased productivity, and less competitiveness in the face of competition among tourism workers in the ASEAN region and internationally. Indonesia with the other nine ASEAN member countries have signed the blueprint declaration of the ASEAN Economic Community to initiate an economic integration step. This makes Bali must strive to improve the quality of tourism human resources as well as enhance the competitiveness of tourism workforce in order to survive in the era of ASEAN free trade and globalization of the international labor market. Bali, in particular, should be able to focus and care about the problem of tourism work and immediately clean up to create a conducive climate to accelerate the movement of economic growth through tourism human resources. This can be done by improving education, improving health, conducting training and developing tourism workforce, providing adequate facilities, improving the labor structure, will encourage the quality of Bali tourism workforce to improve. If a country has the competitiveness and is able to compete in the regional and global arena then it can be assured that the tourism worker is able to achieve standardization and have a good reputation and will certainly increase the national tourism human resource index.